Creation of Breaches, with the Help of Explosives, in Metal Structures under Water and on the Ground Surface - RUS, Simona; KAITER, Edith-Hilde; IFTIMIE, Bogdan; MUNTEANU, Cristian; BURSUC, Andrei; CHIRIAC, Octavian-Gabriel; RUS, NICA (Technium Sustainability, 2022)
The present research-development (CD) paper is a multidisciplinary study requested by the divers belonging to the Diving Center. This study was initiated out of the need to make, with the help of the smallest possible quantities of explosives of very good quality, cutting/sectioning of bars, chains, metal pipes, etc. and breaches of certain shapes and sizes, to enter, as soon as possible, closed enclosures under water (shipwrecks, planes, etc.) in order to recover documents, objects, and so on.